BUILDING GENDER SENSITIVE ATTITUDES: GENDER EQUALITY IN THE WORLD OF EDUCATION - Muhtar; Rukoyah; Pahar Kurniadi (Adisam Publisher, 2024)
One of the demands on the world of education today is justice and gender equality, both in the aspects of access, quality and relevance as well as in the aspect of educational management. The gap in the field of education has become a major factor that greatly influences other fields in Indonesia, almost all sectors, such as employment, positions, roles in society, to the problem of voicing opinions between men and women which is a factor causing gender bias is due to factors Unequal educational gaps are in addition to classic problems that tend to justify injustice, such as the textual interference of religious texts and other socio-cultural obstacles. Various forms of gender disparities that occur in various areas of social life are also presented in the world of education. In fact, educational processes and institutions are seen to play a major role in socializing and perpetuating the values and perspectives that underlie the emergence of various gender inequalities in society.